Targeted inhibition of ANKRD1 disrupts sarcomeric ERK-GATA4 signal transduction and abrogates phenylephrine-induced cardiomyocyte hypertrophy. (13th March 2015) - Zhong, Lin; Chiusa, Manuel; Cadar, Adrian G.; Lin, Angel; Samaras, Susan; Davidson, Jeffrey M.; Lim, Chee C.
Abstract: Aims: Accumulating evidence suggest that sarcomere signalling complexes play a pivotal role in cardiomyocyte hypertrophy by communicating stress signals to the nucleus to induce gene expression. Ankyrin repeat domain 1 (ANKRD1) is a transcriptional regulatory protein that also associates with sarcomeric titin; however, the exact role of ANKRD1 in the heart remains to be elucidated. We therefore aimed to examine the role of ANKRD1 in cardiomyocyte hypertrophic signalling. Methods and results: In neonatal rat ventricular myocytes, we found that ANKRD1 is part of a sarcomeric signalling complex that includes ERK1/2 and cardiac transcription factor GATA4. Treatment with hypertrophic agonist phenylephrine (PE) resulted in phosphorylation of ERK1/2 and GATA4 followed by nuclear translocation of the ANKRD1/ERK/GATA4 complex. Knockdown of Ankrd1 attenuated PE-induced phosphorylation of ERK1/2 and GATA4, inhibited nuclear translocation of the ANKRD1 complex, and prevented cardiomyocyte growth. Mice lacking Ankrd1 are viable with normal cardiac function. Chronic PE infusion in wild-type mice induced significant cardiac hypertrophy with reactivation of the cardiac fetal gene program which was completely abrogated in Ankrd1 null mice. In contrast, ANKRD1 does not play a role in haemodynamic overload as Ankrd1 null mice subjected to transverse aortic constriction developed cardiac hypertrophy comparable to wild-type mice. Conclusion: Our study reveals a novel role for ANKRD1 as a selective regulator of PE-induced signalling whereby ANKRD1 recruits and localizes GATA4 and ERK1/2 in a sarcomeric macro-molecular complex to enhance GATA4 phosphorylation with subsequent nuclear translocation of the ANKRD1 complex to induce hypertrophic gene expression.